ANALISIS SISTEM PEMETIKAN KOPI SELEKTIF DAN RACUTAN TERHADAP PENDAPATAN PETANI KOPI DI KABUPATEN OKU SELATAN - Hariyono (Jurnal Bakti Agribisnis, 2015)
The purpose of this research were to: (1) Determine the cost, revenue, and revenue and profits farmers Robusta coffee with a system of selective and racutan in the district of South OKU, (2) Knowing How large is the ratio of income between the system of picking racutan with the system picking selective in the district of South OKU, (3) Determine the financial feasibility of picking coffee farming system and picking racutan selective system in the district of South OKU. This research was conducted in the District of South OKU. This study was conducted in May and June 2013, with a survey and disproporsionated purposive sampling method, and also took 99 samples. This study found that coffee farming Acceptance by picking racutan system Rp 19,548,148, - / LG and Rp 16,250,776, - / ha, costs Rp 9,159,264, - / LG and Rp 7,578,429, - / ha, the coffee farming with picking system racutan earn Rp 10,388,884, - / LG and 8,672,347, - / ha, whereas usatahani picking coffee with selective system gained acceptance Rp 20,029,412, - / LG and Rp 17,241,947, - / Ha, costs Rp 10.49065 million, - / LG and Rp 8,806,712, - / ha, then the coffee farm picking system selectively obtain revenue of Rp 9,538,762, - / LG and Rp 8,435,234, - / Ha.